2018
DOI: 10.1111/jocn.14350
|View full text |Cite
|
Sign up to set email alerts
|

The meaning of living with uncertainty for people with motor neurone disease

Abstract: Motor neurone disease is a complex disease, and it is important that professionals continue to provide holistic care throughout the illness trajectory. The identification of three distinct phases of the MND illness trajectory will help nurses and other professionals to better understand the meaning of uncertainty and other concerns for people with MND.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 36 publications
3
27
0
Order By: Relevance
“…Similar to patients coping with terminal chronic illnesses, like cancer, neurodegenerative disorders, and multiple morbidities, our study reported the older adults' capacity to overcome EL originated from their own capacity to regulate emotion and re-prioritize goals to concerns when living in the moment in recognition of that loneliness experience could not be changed [43][44][45]. In our study, participants held an adaptive attitude towards EL.…”
Section: Discussionsupporting
confidence: 54%
“…Similar to patients coping with terminal chronic illnesses, like cancer, neurodegenerative disorders, and multiple morbidities, our study reported the older adults' capacity to overcome EL originated from their own capacity to regulate emotion and re-prioritize goals to concerns when living in the moment in recognition of that loneliness experience could not be changed [43][44][45]. In our study, participants held an adaptive attitude towards EL.…”
Section: Discussionsupporting
confidence: 54%
“…Many negative reactions prevailed, including bewilderment, 19 , 20 , 23 , 27 denial 18 20 , 23 , 35 , 51 , 57 and a sense of loss and sadness. 8 , 23 , 37 , 57 At the extremes were people who became very distressed by their position and those who experienced suicidal thoughts: 19 , 20 , 23 , 37 , 39 …”
Section: Resultsmentioning
confidence: 99%
“…Some questioned what had caused the disease, although recognising there may be no clear cause: Ways of maintaining control included managing stress and protecting time for themselves, both as individuals and together. 21,47,49,57 Participants had varying attitudes to how they approached inevitable deterioration, with some wishing to plan ahead 8,20,22,28,29,34,35,39,40,48,54,56,57 and others preferring to live in the present and not consider the future. [22][23][24][25]28,31,[33][34][35]39,40,50,51,56,57 As the disease progressed, both patients and carers tried to find ways to counteract feelings of loss and uncertainty, and to find new meaning in their life: [21][22][23]25,29,35,37,47,49,50,56,57 Determination to do what I can for as long as I can, desire for independence [and a] resilient temperament.…”
Section: Maintaining Controlmentioning
confidence: 99%
See 2 more Smart Citations